2020
DOI: 10.1111/joor.12952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acupuncture on specific and non‐specific points for the treatment of painful temporomandibular disorders: A randomised controlled trial

Abstract: Background and Objective The aim of this single‐centre, two‐arm, parallel‐group, double‐blinded, randomised controlled trial was to investigate the disputed specific effectiveness of acupuncture by comparing acupuncture on specific and non‐specific points among patients with non‐chronic, painful TMDs. Methods Following predefined eligibility criteria, 49 consecutive patients of both sexes were recruited to the study. All subjects were diagnosed with a non‐chronic (Graded Chronic Pain Scale grade <3) painful TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…According to the theory of traditional Chinese medicine, the special acupoint combination can greatly enhance the effect of acupuncture on the gastrointestinal tract. Acupuncture at the acupoints on the disease-affected meridian has been demonstrated to provide superior benefits to patients with temporomandibular disorders, chronic stable angina, functional dyspepsia and migraine 43–46. Therefore, this trial is likely to yield greater benefits than previous similar trials.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to the theory of traditional Chinese medicine, the special acupoint combination can greatly enhance the effect of acupuncture on the gastrointestinal tract. Acupuncture at the acupoints on the disease-affected meridian has been demonstrated to provide superior benefits to patients with temporomandibular disorders, chronic stable angina, functional dyspepsia and migraine 43–46. Therefore, this trial is likely to yield greater benefits than previous similar trials.…”
Section: Discussionmentioning
confidence: 94%
“…Acupuncture at the acupoints on the disease-affected meridian has been demonstrated to provide superior benefits to patients with temporomandibular disorders, chronic stable angina, functional dyspepsia and migraine. 43–46 Therefore, this trial is likely to yield greater benefits than previous similar trials.…”
Section: Discussionmentioning
confidence: 95%
“…Maximum unassisted mouth opening with pain 99,105,111,[113][114][115]120,121,128,130 Muscles pressure pain threshold [101][102][103]115,121,122 Maximum unassisted mouth opening without pai n 97,99,101,103,107,115,116,118,120,121,124,128,130 TMJ pressure pain threshold 102,103,115 Maximum assisted mouth opening 99,115,120,129 TMJ sounds 109,123 Lateral movement The Symptoms and Adverse Events domain was the least evaluated in the studies included in this review, accounting for only 12.3% of the articles. It should be noted that an outcome within this domain was only considered when the authors reported the use of adverse events as an outcome in their study and when appropriate statistical analyses were conducted.…”
Section: Device Measurement Outcomesmentioning
confidence: 99%
“…There were not a few examples of eliminating slight discomfort or minor ailments felt in daily life by pressing acupuncture points [2]. In this study, pressing four acupuncture points selected by the Chat Generative Pretrained Transformer (ChatGPT) (an artificial intelligence chatbot developed by OpenAI Inc.) by giving the efficacy of all acupuncture points in Fig.…”
Section: Objective Of This Studymentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has been an alternative traditional medicine in China [1], [2]. It has been described as pseudoscience with the majority of its treatments appearing to have no logical mechanism of action.…”
Section: Introductionmentioning
confidence: 99%